2020
DOI: 10.1371/journal.pone.0243459
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis, coupling coordination, and efficiency evaluation of green innovation: A case study of the Yangtze River Economic Belt

Abstract: Green innovation is an important driving force to promote the sustainable development of urban society and economy. This paper constructs an evaluation index system containing social undesirable outputs, and uses the Super-SBM model and the Malmquist-Luenberger index to evaluate green innovation efficiency in 42 cities along the Yangtze River Economic Belt from 2013 to 2017. Additionally, spatial autocorrelation analysis is used to study the spatial correlation of green innovation efficiency. Finally, the coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…However, with rapid social and economic development, the contradiction between developing and protecting the YREB has become salient. The YREB faces many problems in need of solutions, including the grim environmental situation, bottlenecks in the Yangtze River waterway, unbalanced regional development, the difficulty of industrial transformation, and poor regional cooperation [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with rapid social and economic development, the contradiction between developing and protecting the YREB has become salient. The YREB faces many problems in need of solutions, including the grim environmental situation, bottlenecks in the Yangtze River waterway, unbalanced regional development, the difficulty of industrial transformation, and poor regional cooperation [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Green development is a theoretical innovation of sustainable development, which balances and coordinates local economic growth, social development and ecological environment improvement [ 2 ]. The green development concept has gained wide currency globally since 2008 [ 1 – 7 ]. Many countries, including the Canada, United Kingdom, Germany and South Korea have invested considerable effort in green, sustainable development—an area that has attracted considerable research attention [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…R&D input (R&D_I). R&D institutions require finances to support innovation, and amount of financial input will affect the efficiency and quality of innovation [53]. 5.…”
mentioning
confidence: 99%
“…As environmental issues in the YREB have been paid more and more attention, Wang et al [15] studied the change of green total factor productivity from the perspective of green technological innovation. Tian et al [16] suggested that green innovation efficiency has a significant positive spatial correlation. Gou et al [17] studied the changes of environmental total factor productivity in the YREB from the perspective of regional green development.…”
Section: Literature Reviewmentioning
confidence: 99%